A Study of Clinical and Laboratory profile of Scrub Typhus in a Tertiary care Teaching Hospital (Academia Journal of Medicine, 2019)
Background: Scrub typhus, also known as bush typhus, is a disease caused by bacteria called Orientatsutsugamushi. This ricketssial infection  is transmitted to humans through the bite of infected heptombidium mite larvae. Subjects and Methods: All patients were subjected to  investigations to establish cause of febrile illness. After complete physical examination, routine laboratory investigations like CBC, serology  for enteric fever, malaria, Scrub typhus and USG abdomen, chest x-ray ,urine analysis and renal function tests were done in all patients. In all  cases diagnosis was based on detection of antibodies using a single step rapid immunochromatography method. Results: 120 patients, who  were admitted with undifferentiated acute febrile illness during the study period diagnosed to be suffering from Scrub typhus with positive  antibodies, the following results were noted. Fever was the most common symptom seen in all the 120 patients (100%). The duration of fever  ranging from one to seven days was present in 94 patients (78.3%), fever for 7-12days present in 5 patients(4.2%) and fever for more than 2  weeks was present in 5 patients(4.12%). Headache and vomitings were the commonly associated symptoms. Generalized muscle pain  (myalgia) was present in 63patients(52.5%). Headache was present in 64 patients (53.3%), diarrohea was complained by 2 patients(1.7%),  vomiting in 47patients(39.2%), shortness of breath was present in 16 patients(13.3%), abdominal pain was present in 17patients(14.2%) and  skin rash was seen in 1 patient(0.8%). Conclusion: Majority of the cases of Scrub typhus are seen in the cooler months of the year and in the  rainy season. It has to be considered in the differential diagnosis of undifferentiated acute febrile illness.
Keywords: Clinical symptom & Scrub typhus